A method for preparing foamed carbon using sodium bicarbonate as a foaming agent

By using sodium bicarbonate as a foaming agent and weakly basic hexadecimal methyltetramine as a curing agent, the problems of poor pore structure uniformity and insufficient mechanical properties of foam carbon materials are solved, and safe and efficient foam carbon preparation is achieved. Have the potential for large-scale production.

CN116081596BActive Publication Date: 2024-12-17INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210993307.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-18
Publication Date
2024-12-17
Estimated Expiration
2042-08-18

AI Technical Summary

Technical Problem

The existing foam carbon material preparation methods have problems such as poor pore structure uniformity, insufficient mechanical bearing performance, high safety risks, complex preparation process and high cost. Especially traditional foaming agents are volatile or flammable, and there are potential dangers under high temperature and high pressure conditions. , and the sample batch stability is insufficient.

Method used

Sodium bicarbonate (NaHCO3) is used as the foaming agent, and CO2 gas is generated to form a uniform pore structure by regulating the resin viscosity and temperature field, and weakly alkaline hexadecimal methyltetramine is used as the curing agent to reduce the curing reaction rate and improve the organic The cross-linking degree of the framework is obtained by carbonization and obtaining foam carbon materials with uniform pore structure and excellent mechanical properties.

Benefits of technology

It has achieved improvements in pore structure uniformity and mechanical properties, simplified the preparation process, reduced costs, avoided the safety risks of traditional foaming agents, and had the potential for large-scale production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0003804457680000011
    Figure HDA0003804457680000011
  • Figure HDA0003804457680000012
    Figure HDA0003804457680000012
Patent Text Reader

Abstract

The present invention discloses a method for preparing foamed carbon using sodium bicarbonate as a foaming agent, and belongs to the technical field of porous material preparation. The method comprises the following steps: (1) uniformly mixing a foaming agent, a surfactant, a curing agent, etc. with a carbon-rich medium to form a precursor solution; (2) pouring the precursor solution into a stainless steel mold, and then placing the mold in a vacuum drying oven for foaming and curing to obtain an organic foam precursor; (3) then drying, demoulding, carbonizing or graphitizing to obtain a foamed carbon sample. The NaHCO 3 The foaming agent is safe, efficient, and has no toxic side effects. It can effectively replace traditional liquid foaming agents, solving the problem that low-boiling point liquid foaming agents are extremely volatile at room temperature, causing the foaming agent to fail, and avoiding the potential danger of liquid foaming agent vapor and air forming an explosive mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of porous material preparation, and in particular to a method for preparing foamed carbon using sodium bicarbonate as a foaming agent. Background Art

[0002] The rapid development of science and technology has put forward higher service requirements for the characteristics of materials. Many traditional materials with single performance have gradually been unable to meet the actual application needs. Therefore, some new functional structural materials have gradually emerged with the increase in demand. In recent years, porous carbon foam, as a hot spot in the research field of lightweight functional structural materials, has made great progress in various frontier material fields. It is a porous material with a three-dimensional macroscopic structure, with the characteristics of high conductivity, large specific surface area, high porosity, good heat resistance, low cost, adjustable density and pore size, design of special-shaped parts and diversified precursors. Therefore, the structural materials with different functionalities obtained after treatment and modification based on porous carbon carriers can have broad application prospects in many civil and military fields such as energy storage, electronic devices, aerospace, environmental protection and thermal control management. However, porous carbon materials represented by carbon foam still face difficulties in achieving uniform pore structure, orderly microstructure, adjustable pore size gradient, excellent mechanical bearing performance and engineering amplification. Based on the above key scientific issues, whether considering the matrix itself or as a multifunctional structural carrier after modification, foam carbon materials should be effectively regulated in terms of precursor selection, structural design, and safer, simpler and more efficient preparation methods, so as to meet the application requirements in different fields.

[0003] The classification of foamed carbon mainly includes biomass-based foamed carbon, mesophase asphalt-based foamed carbon and coal-based asphalt foamed carbon. Among them, the preparation methods of mesophase asphalt and coal-based asphalt foamed carbon are similar. The bubble nuclei generated by the escaped light components or the first decomposed gas merge, aggregate and expand under the driving force of the surface energy and the pressure difference between the inside and outside of the bubble, and finally form spherical bubbles under the action of surface tension. This process requires the help of a complex high-pressure environment, which consumes energy and is extremely dangerous. In recent years, carbonization of organic polymer foam is one of the effective ways to prepare foamed carbon. This method mainly prepares non-graphitized foamed carbon with low thermal conductivity. Compared with the high-porosity foamed carbon prepared by the template method, this method has made breakthrough progress in mechanical properties and adjustable pore structure. Because it mainly changes the viscosity of the resin polymer, under a certain pressure, the temperature is raised to the molten state of the polymer resin, and the foaming agent is rapidly foamed to produce gas. When the gas escapes, pores with window-like shapes are left, and then the foamed carbon material is obtained through curing, carbonization or graphitization and other process steps. Although this method can effectively obtain the target product, it still faces many harsh problems in the process of practical application and engineering scale-up. On the one hand, the traditional foaming agents used are mainly some low-boiling point liquid foaming agents, such as n-hexane. Even at room temperature, such foaming agents are very volatile, which leads to foaming failure. Secondly, the vapor of the foaming agent (such as n-pentane, etc.) can form an explosive mixture with the air. When exposed to open flames or high heat, it is very easy to burn and cause explosion, posing a potential safety risk. In addition, under high temperature and high pressure, the regulation of pore structure by pressure relief method still has a high risk, and the stability of sample batches is insufficient. On the other hand, the curing agents used in most reported methods are mostly strong acids (H 2 SO 4 , HCl, HNO 3 , H 3 PO 4 、p-CH 3 C 6 H 4 SO 3 H, etc.), strong bases (NaOH, KOH) or a variety of mixed solvents, participate in the reaction before being fully mixed with the resin mixture during application. The violent exothermic reaction will generate a high amount of heat in a short time. The uneven temperature field in the curing area causes the foaming agent to cure immediately without fully acting in the system. The entire reaction process is difficult to control, resulting in poor uniformity of the pore structure of the prepared foam carbon. The carbonized samples are also difficult to apply in the fields of thermal control devices, energy environment, etc.

[0004] To the best of the authors' knowledge, no studies have been conducted using NaHCO 3 Based on this, the present invention aims to add a small amount of NaHCO, which is safe and has no toxic side effects, to the resin. 3As a foaming agent, it changes the viscosity of the resin at a certain temperature. The foaming agent decomposes in its molten state to produce CO 2 Gas, when the gas escapes, leaves behind a uniformly shaped pore structure. Weakly alkaline hexamethylenetetramine is used as a curing agent to effectively reduce the curing reaction rate of the resin and increase the crosslinking degree of the organic skeleton. After carbonization treatment, a lightweight multifunctional foam carbon material with uniform pore structure and excellent mechanical properties is obtained. The preparation method is simple to operate, has a short preparation cycle and low cost, and is expected to be used as an energy carrier or special-shaped structural parts, and has the potential for large-scale production and application. Summary of the invention

[0005] The purpose of the present invention is to provide a simple, low-cost and more universal method for preparing foamed carbon using sodium bicarbonate as a foaming agent, so as to solve the problems of many preparation defects, large system limitations, complicated and unstable process and long process in the existing method.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing foamed carbon using sodium bicarbonate as a foaming agent, the method comprising the following steps:

[0008] (1) Preparation of resin mixed solution: adding resin, diluent, foaming agent, surfactant and curing agent in proportion, stirring and mixing until fully dissolved to obtain a uniform resin mixed solution, which is the precursor solution system;

[0009] (2) pouring the precursor solution obtained in step (1) into a stainless steel mold with a release cloth attached thereto, and then placing it in a vacuum drying oven for foaming and curing to obtain an organic foam precursor;

[0010] (3) The prepared organic foam precursor is carbonized under an inert atmosphere to obtain foam carbon materials with different carbon crystallinity and graphitization degree.

[0011] In the above step (1), the resin is one or more carbon-rich resins such as phenolic resin, furan resin, silicone resin, condensed polynuclear aromatic resin and polyarylacetylene resin; or the resin is modified and used (such as boron phenolic resin).

[0012] In the above step (1), the diluent is used to reduce the viscosity of the resin, and the diluent is an inorganic solvent and / or an organic solvent; the inorganic solvent is deionized water, and the organic solvent is one or more of methanol, ethanol, ethylene glycol, acetonitrile, ethylenediamine, isopropanol, glycerol (glycerin) and petroleum ether.

[0013] In the above step (1), the foaming agent is NaHCO 3In order to prevent the weak solubility and dispersibility of powder from agglomerating after direct addition, which will affect the uneven nucleation of some foaming sites, NaHCO 3 The powder is ground into uniform fine particles; in addition, the curing agent used is weakly alkaline hexamethylenetetramine, which is also fully ground and added to the mixed solution system. After stirring and mixing evenly, a surfactant (foam leveler) is immediately added, and the surfactant is Tween-80 or Span-80.

[0014] In the above step (1), the mass ratio of the resin, diluent, foaming agent, surfactant (foam leveling agent) and curing agent is (10-200): (1-800): (1-60): (1-60): (1-60).

[0015] In the above step (2), during curing, a heat source such as a vacuum drying oven, a water bath, an oil bath, a heating jacket, a heating table, etc. can be used to heat the system for foaming and curing; the entire foaming and curing process is divided into four stages, the temperature range of the first stage is 15°C-60°C, the heating rate is 0.5°C / min-20°C / min, and the insulation time is 1h-8h; the temperature range of the second stage is 50°C-80°C, the heating rate is 0.5°C / min-20°C / min, and the insulation time is 2h-20h; the temperature range of the third stage is 60°C-160°C, the heating rate is 0.5°C / min-30°C / min, and the insulation time is 1h-100h; the temperature range of the fourth stage is 70°C-180°C, the heating rate is 0.5°C / min-30°C / min, and the insulation time is 1h-30h.

[0016] After the foaming and curing treatment in step (2), the obtained organic foam precursor can be ultrasonically cleaned three times using acetone, deionized water and ethanol in sequence to remove residual impurities and oil stains, and then placed in a vacuum drying oven for drying treatment at a temperature of 30° C.-180° C. for a treatment time of 2 h-100 h; after the drying treatment, the carbonization process in step (4) is performed.

[0017] In the above step (3), the inert atmosphere used during carbonization is nitrogen or argon, and its flow rate is 2mL / min-200mL / min; the carbonization process is mainly divided into four stages: the temperature range of the first stage is 15℃-400℃, the heating rate is 0.5℃ / min-50℃ / min, and the insulation time is 0.1h-10h; the temperature range of the second stage is 200℃-900℃, the heating rate is 0.5℃ / min-50℃ / min, and the insulation time is 0.1h-30h; the temperature range of the third stage is 600℃-1200℃, the heating rate is 0.5℃ / min-50℃ / min, and the insulation time is 0.1h-20h; the temperature range of the fourth stage is 800℃-1500℃, the heating rate is 0.5℃ / min-50℃ / min, and the insulation time is 1h-20h.

[0018] In the above step (3), non-graphitized foamed carbon is obtained after low-temperature carbonization, which can be graphitized continuously or the non-graphitized sample can be taken out and graphitized separately. The treatment temperature range is 1500°C-2600°C, the heating rate is 5°C / min-60°C / min, and the insulation time is 1h-30h.

[0019] In the above step (3), after obtaining the organic polymer foam in step (3) (organic foam precursor), cutting, grinding, cleaning and other treatments can be performed first, and foam carbon of different sizes can be directly obtained after carbonization or graphitization is completed; or after carbonization, the obtained foam carbon material can be cut, polished and other treatments to obtain a foam carbon sample with the required structure.

[0020] The sample prepared by the method of the present invention is a lightweight porous foam carbon material, the surface of which is hydrophilic, but due to its pore structure and low density, when placed in an aqueous solution, it can float on the surface of the solution.

[0021] The foamed carbon is a three-dimensional lightweight functional porous carbon material composed of pores and pore walls, which is obtained by foaming, curing, demoulding, carbonization and graphitization processes with a carbon-rich resin slurry as a precursor. According to its carbonization temperature, it can be divided into graphitized and non-graphitized foamed carbon. By regulating the relative proportions between polymer resin, foaming agent, surfactant (foaming agent), diluent solvent and curing agent, foamed carbon materials of different densities and strengths are obtained. When the content of the foaming agent in the mixed solution is increased, the number of pores increases, the foaming space between adjacent pores is limited, and the pore size of the foamed carbon becomes smaller. In addition, the addition of a diluent solvent can reduce the viscosity of the resin mixed solution, which can effectively regulate the density of the foamed carbon material. After parameter optimization, a foamed carbon material with a pore size range of 150 μm to 300 μm can be prepared, the pores are evenly distributed, the pores are mainly bonded by the resin carbon surface area, and has excellent mechanical bearing properties and adjustable microstructure.

[0022] The design mechanism of the present invention is as follows:

[0023] The present invention is to use sodium bicarbonate (NaHCO 3 ) is used as a foaming agent for the preparation and application of carbon foam, in order to solve the problems of uneven pore size, single structure, poor mechanical bearing capacity, and thermal stress generated at high temperature during the carbonization process, which leads to collapse of the pore structure and cracking of the skeleton of the carbon foam sample, making it difficult to be used in thermal control devices and energy carriers.

[0024] The preparation process and characteristics of the material in the present invention are as follows: (1) a foaming agent, a surfactant and a curing agent are mixed evenly with a carbon-rich medium by a pyrolysis foaming method to form a precursor solution system; (2) the viscosity of the precursor solution is adjusted by controlling the temperature under normal pressure. When the system is in a molten state, NaHCO 3 Acting as a pore-forming agent, it is very easy to decompose and produce a large amount of CO when heated. 2 As the gas continuously escapes from bottom to top, the precursor solution leaves a uniform pore structure, and after solidification, an organic precursor foam with a uniform pore structure and rich pores is obtained; (3) the foam carbon sample is obtained after drying, demolding, carbonization or graphitization. The NaHCO 3 The foaming agent is safe and efficient, with no toxic side effects. It can effectively replace traditional liquid foaming agents (such as n-pentane, n-hexane and other low-boiling point foaming agents), solving the problem that low-boiling point liquid foaming agents are extremely volatile at room temperature, which leads to the failure of the foaming agent, and avoiding the potential danger of liquid foaming agent vapor and air forming an explosive mixture. The prepared sample is a microspherical lightweight foam carbon with a pore size range of 100μm to 300μm. The pores are evenly distributed, and the pores are not in traditional point contact, but in surface contact with resin carbon as the bonding area, thereby significantly improving the intrinsic strength of the foam carbon skeleton. The foam carbon sample prepared by this method has a uniform pore structure, a simple, safe and efficient preparation process, a short preparation cycle and low cost, and has the potential for large-scale engineering applications.

[0025] The advantages and beneficial effects of the present invention are:

[0026] 1. The present invention is a method of using NaHCO which is cheap, simple, efficient, safe and reliable 3 It is used as a foaming agent for foaming, and the density of the material is controlled by regulating the temperature field and dosage ratio of the foaming environment, which solves the problems of many defects in the pore structure of the foamed carbon obtained by the existing preparation method, cumbersome and complicated synthesis process, and high risk of preparation operation.

[0027] 2. The resin used in the method of the present invention is not limited to a specific resin, and the pore size and distribution state of the foamed carbon can be effectively regulated by changing the resin type and the amount of the foaming agent.

[0028] 3. The sample prepared by the method of the present invention is a lightweight porous foam carbon. The carbon material shows hydrophilic properties. Due to its light weight, low density, and mesoscopic closed-pore properties, when it is placed in an aqueous solution, the foam carbon floats on the surface of the solution.

[0029] 4. The present invention uses industrial-grade resin as the main raw material, which reduces the cost of raw materials. In addition, the lightweight foam carbon material prepared by the present invention has excellent mechanical properties, and the thermal conductivity of the material can be regulated by low-temperature carbonization or high-temperature graphitization. The present invention can prepare a foam carbon material with a specific size and structure according to the size and shape of the mold. The whole method is easy to operate, the process flow is simple, and it has the potential for large-scale production and application. The prepared foam carbon can be used as an energy carrier or a thermal control device. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Macroscopic photographs of the foam precursor prepared by the mold and after carbonization; among them: (a) is the phenolic organic foam prepared with a 500mL beaker as the mold; (b) is the block foam carbon material obtained after the sample is carbonized at 1100℃, cut and polished.

[0031] Figure 2 The figures are macroscopic photographs of carbon foam under different preparation conditions; among them: (a) is the prepared mixed phenolic resin solution; (b) and (c) are phenolic organic polymer foams after foaming and curing; (d) is the carbon foam material obtained by carbonization treatment at 1100°C; (e) is the macroscopic morphology of the cross section of the block carbon foam; (f) is the carbon foam after the sample is cut, polished, ultrasonically cleaned and dried.

[0032] Figure 3 This is an electron scanning photograph of non-graphitized carbon foam obtained by carbonization treatment at 1100℃.

[0033] Figure 4 This is an electron scanning photograph of foam carbon obtained by graphitization treatment at 2300℃.

[0034] Figure 5 XRD patterns of carbon foam samples obtained by carbonization at 1100℃ and graphitization at 2300℃.

[0035] Figure 6 Macroscopic photos of carbon foam samples floating on the surface of water and their contact angles with water; (a) and (b) are the floating states of carbon foam samples in water; (c) is the contact angle of carbon foam with water.

[0036] Figure 7 The foam carbon samples were prepared in a cylindrical mold; (a) is the sample carbonized at 1000°C; (b) is the mass of the sample after carbonization; (c) is the macroscopic photograph of the sample after slicing.

[0037] Figure 8 Mechanical bearing properties of carbon foam. DETAILED DESCRIPTION

[0038] In order to further understand the present invention, the present invention is described below in conjunction with examples, but the examples are only for further elaboration of the features and advantages of the present invention, rather than for limitation of the claims of the present invention.

[0039] The present invention converts NaHCO into a safe and non-toxic 3 As a foaming agent, it is introduced into the resin mixed solution to adjust the viscosity of the resin to a molten state by changing the temperature. 3 Decomposition produces CO 2 Gas, when the gas escapes, leaves behind a uniform pore structure, weakly alkaline hexamethylenetetramine is used as a curing agent to cure the polymer foam, and then a porous foam carbon material with uniform pore structure and excellent mechanical bearing properties is obtained through carbonization treatment.

[0040] The method of the present invention specifically comprises the following steps:

[0041] (1) firstly preparing an organic polymer resin precursor mixed solution, adding a polymer resin, a diluent solvent, a foaming agent, a surfactant and a curing agent in corresponding proportions, and mixing them thoroughly until they are dissolved to obtain a uniform resin mixed solution;

[0042] (2) transferring the mixed solution obtained in step (1) into a mold with a release cloth attached thereto, and then placing it in a drying oven for full foaming and slow curing to obtain a polymer resin foam;

[0043] (3) After the mixed resin solution in step (2) is foamed and cured, the obtained organic resin foam can be rinsed three times with acetone, deionized water and ethanol in sequence to remove residual impurities and oil stains, and then placed in a drying oven to dry (this step can be omitted);

[0044] (4) placing the polymer resin foam prepared in step (3) into a graphite crucible, and then placing it in a carbonization furnace protected by an inert atmosphere for annealing, and after carbonization is completed and cooled to room temperature, obtaining a heat-insulating foam carbon material;

[0045] (5) The carbon foam obtained by carbonization in step (4) is subjected to high-temperature graphitization treatment to obtain a thermally conductive carbon foam material with high thermal conductivity.

[0046] In step (1), the precursor resin may include: phenolic resin, furan resin, silicone resin, condensed polynuclear aromatic resin and polyarylacetylene resin and other carbon-rich precursors. The above resins may also be modified to obtain boron phenolic resin, or derivatives of mixed solutions of various resins as precursors for preparing foamed carbon.

[0047] In step (1), the diluting solvent for reducing the viscosity of the resin can be an inorganic solvent such as deionized water, and an organic solvent includes methanol, ethanol, ethylene glycol, acetonitrile, ethylenediamine, isopropanol, glycerol (glycerin) and petroleum ether, or can be prepared by mixing the above solvents.

[0048] In step (1), during the mixing and stirring process, a foaming agent NaHCO is added. 3 , surfactant Tween-80 or Span-80, curing agent is weak alkaline hexamethylenetetramine. In order to make the mixed system dissolve quickly, it should be fully ground before adding the resin solution, and it can be used only after it is completely dissolved.

[0049] In step (1), the mass ratio of the resin solution, the diluent solvent, the foaming agent, the surfactant and the curing agent is (10-200): (1-800): (1-60): (1-60): (1-60).

[0050] In step (2), a heat source such as a vacuum drying oven, a water bath, an oil bath, a heating jacket, a heating table, etc. can be used during curing to gently foam the precursor solution and slowly cure it. The process is divided into four stages. The temperature range of the first stage is 15°C-60°C, the heating rate is 0.5°C / min-20°C / min, and the insulation time is 1h-8h; the temperature range of the second stage is 50°C-80°C, the heating rate is 0.5°C / min-20°C / min, and the insulation time is 2h-20h; the temperature range of the third stage is 60°C-160°C, the heating rate is 0.5°C / min-30°C / min, and the insulation time is 1h-100h; the temperature range of the fourth stage is 70°C-180°C, the heating rate is 0.5°C / min-30°C / min, and the insulation time is 1h-30h.

[0051] In step (3), after foaming, curing and demoulding, the prepared polymer foam is washed three times with acetone, deionized water and ethanol in sequence, and then placed in a drying oven for drying at a temperature of 30° C. to 180° C. for a drying time of 2 h to 100 h.

[0052] In step (4), the inert atmosphere used during carbonization is nitrogen or argon, and its flow rate is 2mL / min-200mL / min. The carbonization process is divided into four stages. The temperature range of the first stage is 15°C-400°C, the heating rate is 0.5°C / min-50°C / min, and the insulation time is 0.1h-10h; the temperature range of the second stage is 200°C-900°C, the heating rate is 0.5°C / min-50°C / min, and the insulation time is 0.1h-30h; the temperature range of the third stage is 600°C-1200°C, the heating rate is 0.5°C / min-50°C / min, and the insulation time is 0.1h-20h; the temperature range of the fourth stage is 800°C-1500°C, the heating rate is 0.5°C / min-50°C / min, and the insulation time is 1h-20h, and the carbonization is completed after finally cooling to room temperature.

[0053] In step (5), non-graphitized foamed carbon is obtained after low-temperature carbonization, which can be directly subjected to high-temperature graphitization treatment, or the sample can be taken out and graphitized separately. The temperature treatment range is 1500°C-2600°C, the heating rate is 5°C / min-60°C / min, and the insulation time is 1h-30h.

[0054] The present invention is further described in detail below through examples and drawings.

[0055] Example 1

[0056] In this example, NaHCO 3 The preparation of foamed carbon as a foaming agent comprises the following steps:

[0057] The pre-ground NaHCO 3 The foaming agent is added to a mixed solution containing 5g of deionized water and 10g of propylene glycol (glycerol), and the mixture is stirred thoroughly until completely dissolved and marked as solution A. 80g of phenolic resin is weighed and poured into a 500mL beaker, and stirred continuously at a stirring speed of 400r / min for 0.5h. Then, the pre-prepared solution A is added, and stirring is continued for 0.5h at room temperature. Then, 3g of hexamethylenetetramine is added to the mixed solution. After dissolution, the precursor solution is uniformly brown-yellow, and 10g of Tween-80 is added after the color no longer changes. After the mixed solution is completely dissolved, the precursor solution is prepared.

[0058] The prepared precursor solution was transferred to a 500 mL beaker and then placed in a drying oven for foaming and curing. 3 When heated to above 50°C, it begins to gradually decompose and generate Na 2 CO 3 , CO 2 and H 2O, can be completely decomposed at 150°C. Therefore, the foaming and curing process can be divided into four stages: (1) room temperature to 60°C, heating rate of 2°C / min, heat preservation for 3h; (2) 60°C-80°C, heating rate of 5°C / min, heat preservation for 8h; (3) 80°C-120°C, heating rate of 10°C / min, heat preservation for 6h; (4) reduce to 90°C for drying and keep warm for 48h.

[0059] like Figure 1 As shown in a, after the phenolic foam is dried, the sample is carbonized and heated to 1100°C at a rate of 5°C / min under argon protection. After 2 hours of heat preservation, a non-graphitized carbon foam material is obtained. Figure 1 As shown in b, the prepared foam carbon has a uniform pore structure on a macro scale and has no obvious preparation defects.

[0060] Figure 2 Macroscopic photos of foam carbon under different preparation conditions.

[0061] Figure 3 The scanning photos in the figure show that the non-graphitized foam carbon obtained after carbonization at 1100°C has a smooth carbon wall surface without obvious cracks and impurities, the structure of the pores is intact and the microstructure is uniform, the pore size range is mainly distributed between 150μm and 300μm, and the multiple pores of the sample are mainly bonded by resin carbon.

[0062] Example 2

[0063] In this embodiment, non-graphitized carbon foam was used as a comparison, and the carbon foam was placed in a high temperature furnace at a heating rate of 30° C. / min to 2300° C. and kept at that temperature for 1 hour to prepare graphitized carbon foam. Figure 4 These are scanning photos of the graphitized foamed carbon obtained after carbonization at 2300℃ at different magnifications. It can be seen that its microstructure has not changed significantly. Figure 5 The XRD patterns of carbon foam samples carbonized at 1100℃ and graphitized at 2300℃ are compared with the standard card PDF#41-1487. The analysis shows that after the carbon foam samples are graphitized at high temperature, the (002) and (100) diffraction peaks of the samples become sharper, proving that the crystallinity of the carbon foam samples is significantly improved. Figure 6 a and b are macroscopic photos of the carbon foam sample floating on the surface of the water liquid, Figure 6 c is the contact angle test of carbon foam and aqueous solution. The results show that the contact angle θ is 62°, indicating that the surface of carbon foam is hydrophilic. However, due to its light weight and low density structural characteristics, when it is placed in aqueous solution, carbon foam can float on the surface of the solution, further proving that the sample is a lightweight porous microsphere carbon foam.

[0064] Example 3

[0065] The pre-ground NaHCO 3 The powder foaming agent is added to 40g of deionized water and 120g of propylene glycol (glycerol), stirred until dissolved and marked as solution B; 600g of phenolic resin is weighed and poured into a 1L beaker, stirred at a speed of 600r / min for 1h, and then the pre-prepared solution B is added and stirred at room temperature for 2h. 35g of curing agent hexamethylenetetramine is added to the mixed solution and stirred for 1.5h. After the solution is completely dissolved and the precursor solution is brown-yellow and the color no longer changes, 110g of surfactant Span-80 is added. After the system is completely mixed, the precursor solution is prepared.

[0066] The prepared precursor solution was transferred to a square box mold and placed in a drying oven for foaming and curing. The process temperature parameters can be divided into four stages: (1) room temperature to 80°C, heating rate of 10°C / min, and heat preservation for 6 h; (2) 80°C-100°C, heating rate of 2°C / min, and heat preservation for 5 h; (3) 100°C-140°C, heating rate of 10°C / min, and heat preservation for 12 h; (4) reducing the temperature to 120°C for drying and heat preservation for 72 h.

[0067] After the phenolic foam is dried, due to the large size of the sample, in order to prevent the sample from cracking due to the excessively fast heating rate during the carbonization process, the carbonization heating rate needs to be slowed down. 2 Under protection, the temperature was raised to 350℃ at a rate of 2℃ / min and kept for 1h; then, 350℃-800℃, the temperature was raised at a rate of 5℃ / min, and kept for 0.5h; finally, 800℃-1000℃, the temperature was raised at a rate of 10℃ / min, and kept for 2h. The specific state of the sample is as follows Figure 2 As shown in d, 2e and 2f, after the reaction is completed, the temperature is cooled to room temperature, and then the sample is cut, polished, ultrasonically cleaned, etc. to obtain foamed carbon material.

[0068] like Figure 7 As shown in the figure, using the same preparation method, only the square box mold is replaced with a cylindrical mold, the pore structure of the prepared carbon foam sample is also uniform, and there are no obvious preparation defects. More importantly, it can still show ultra-lightweight structural characteristics at a large size ( Figure 7 b). When the sample was cut into thinner disc structures, there was no significant negative impact on its structure ( Figure 7 c).

[0069] The test results show that the volume density of the sample is about 0.18g / cm 3 .like Figure 8 As shown, 1*1*1cm 2The carbon foam sample of the size can easily bear the weight of 500g weight, indicating that the sample has excellent mechanical bearing performance. As shown in Table 1, at room temperature, the average thermal conductivity of the non-graphitized carbon foam in the z direction is 0.1041W / m·K, indicating that the prepared carbon foam material has outstanding thermal insulation performance.

[0070] Table 1 Thermal conductivity of carbon foam at room temperature

[0071]

[0072] In summary, the results of the embodiments show that the present invention provides a method of preparing a NaHCO 3 Preparation and application of porous carbon foam as a foaming agent, which can effectively utilize NaHCO 3 As a foaming agent, a microspherical lightweight porous carbon foam material with uniform pore structure, adjustable pore size and excellent mechanical bearing performance is prepared. Compared with the reported carbon foam preparation method, this method is simple to operate, safe and efficient, low cost and has a wide range of applications. It can provide an important reference for the preparation of other porous structure materials in the future and has practical scale promotion value.

Claims

1. A method for preparing foamed carbon using sodium bicarbonate as a foaming agent, Features: The method comprises the following steps: (1) Preparation of resin mixed solution: Add resin, diluent, foaming agent, surfactant and curing agent in proportion, stir and mix until fully dissolved to obtain a uniform resin mixed solution, which is the precursor solution; (2) pouring the precursor solution obtained in step (1) into a stainless steel mold with a release cloth attached thereto, and then placing it in a vacuum drying oven for foaming and curing to obtain an organic foam precursor; (3) carbonizing the prepared organic foam precursor under an inert atmosphere to obtain foamed carbon materials with different carbon crystallinity and graphitization degree; In step (1), the resin is one or more of phenolic resin, furan resin, silicone resin, condensed polynuclear aromatic resin and polyarylacetylene resin; or the carbon-rich resin is modified and used; In step (1), the foaming agent is NaHCO 3 In order to prevent the weak solubility and dispersibility of powder from agglomerating after direct addition, which will affect the uneven nucleation of some foaming sites, NaHCO 3 The powder is ground into uniform fine particles; in addition, the curing agent used is weakly alkaline hexamethylenetetramine, which is also fully ground and added to the mixed solution system. After stirring and mixing evenly, a surfactant is immediately added, and the surfactant is Tween-80 or Span-80.

2. The method for preparing foamed carbon using sodium bicarbonate as a foaming agent according to claim 1, Features: In step (1), the diluent is used to reduce the viscosity of the resin, and the diluent is an inorganic solvent and / or an organic solvent; the inorganic solvent is deionized water, and the organic solvent is one or more of methanol, ethanol, ethylene glycol, acetonitrile, ethylenediamine, isopropanol, glycerol and petroleum ether.

3. The method for preparing foamed carbon using sodium bicarbonate as a foaming agent according to claim 1, Features: In step (1), the mass ratio of the resin, diluent, foaming agent, surfactant and curing agent is (10-200): (1-800): (1-60): (1-60): (1-60).

4. The method for preparing foamed carbon using sodium bicarbonate as a foaming agent according to claim 1, Features: In step (2), during curing, the system can be heated to foam and cure using a vacuum drying oven, a water bath, an oil bath, a heating jacket, or a heating table heat source; the entire foaming and curing process is divided into four stages, the temperature range of the first stage is 15°C-60°C, the heating rate is 0.5°C / min-20°C / min, and the insulation time is 1h-8h; the temperature range of the second stage is 50°C-80°C, the heating rate is 0.5°C / min-20°C / min, and the insulation time is 2h-20h; the temperature range of the third stage is 60°C-160°C, the heating rate is 0.5°C / min-30°C / min, and the insulation time is 1h-100h; the temperature range of the fourth stage is 70°C-180°C, the heating rate is 0.5°C / min-30°C / min, and the insulation time is 1h-30h.

5. The method for preparing foamed carbon using sodium bicarbonate as a foaming agent according to claim 1, Features: After the foaming and curing treatment in step (2), the obtained organic foam precursor is ultrasonically cleaned three times with acetone, deionized water and ethanol in sequence to remove residual impurities and oil stains, and then placed in a vacuum drying oven for drying treatment at a temperature of 30° C. to 180° C. for a treatment time of 2 h to 100 h; after the drying treatment, the carbonization process in step (3) is carried out.

6. The method for preparing foamed carbon using sodium bicarbonate as a foaming agent according to claim 1, Features: In step (3), the inert atmosphere used during carbonization is nitrogen or argon, and its flow rate is 2mL / min-200mL / min; the carbonization process is mainly divided into four stages: the temperature range of the first stage is 15℃-400℃, the heating rate is 0.5℃ / min-50℃ / min, and the insulation time is 0.1h-10h; the temperature range of the second stage is 200℃-900℃, the heating rate is 0.5℃ / min-50℃ / min, and the insulation time is 0.1h-30h; the temperature range of the third stage is 600℃-1200℃, the heating rate is 0.5℃ / min-50℃ / min, and the insulation time is 0.1h-20h; the temperature range of the fourth stage is 800℃-1500℃, the heating rate is 0.5℃ / min-50℃ / min, and the insulation time is 1h-20h.

7. The method for preparing foamed carbon using sodium bicarbonate as a foaming agent according to claim 1, Features: In step (3), non-graphitized foamed carbon is obtained after low-temperature carbonization, and the graphitization treatment can be carried out continuously, or the non-graphitized sample can be taken out and graphitized separately. The treatment temperature range is 1500°C-2600°C, the heating rate is 5°C / min-60°C / min, and the insulation time is 1h-30h.

8. The preparation and application of foamed carbon using sodium bicarbonate as a foaming agent according to claim 1, Features: In step (3), the organic foam precursor obtained in step (2) can be cut, polished, and cleaned first, and foam carbon of different sizes can be directly obtained after carbonization or graphitization. Alternatively, the obtained foam carbon material can be cut and polished after carbonization to obtain a foam carbon sample with the required structure.